Color change and emission of volatile organic compounds from Scots pine exposed to heat and vacuum-heat treatment - SivriKaya, Hüseyin; Tesarova, Daniela; Jerabkova, Eva; Can, Ahmet; Can, Ahmet (Elsevier, 2019)
Heat treatment improves the dimensional stability and durability of wood. Thermal modification of wood has been extensively studied in the last two decades as it is an environmentally friendly method. Thermally treated wood has been industrialized under different brand names such as ThermoWood, Plato wood and Retified wood. These products differ from each other according to their process technology. During the heat treatment process, wood is chemically changed due to the higher temperature. This is followed by increased color change and the wood becomes darker. In addition, various volatile organic compounds (VOCs) in different quantities are emitted during or after heat treatment. In this study, evaluation of VOC emissions of Scots pine sapwood and heartwood was carried out after heat and vacuum-heat treatment. Higher mass loss occurred in sapwood samples with heat treatment as compared to vacuum-heat treatment. Lightness decreased and color change increased after the heat treatment, but these results were inhibited with vacuum-heat treatment. Vacuum-heat treatment increased the sum of emitted compounds (TVOC) when heartwood samples were used. Pentanal, hexanal and alpha-Pinene were emitted from air-dried samples in higher quantities than other compounds, with alpha-Pinene being the most frequently emitted compound from the air-dried or treated wood samples.
Keywords: Scots Pine; Heat Treatment; Voc; Mass Loss; Color Change